The role of nanomaterials in redox-based supercapacitors for next generation energy storage devices. - Zhao, X; Sánchez, B; Dobson, P; Grant, P (2011)
The development of more efficient electrical storage is a pressing requirement to meet future societal and environmental needs. This demand for more sustainable, efficient energy storage has provoked a renewed scientific and commercial interest in advanced capacitor designs in which the suite of experimental techniques and ideas that comprise nanotechnology are playing a critical role. Capacitors can be charged and discharged quickly and are one of the primary building blocks of many types of electrical circuit, from microprocessors to large-sale power supplies, but usually have relatively low energy storage capability when compared with batteries. The application of nanostructured materials with bespoke morphologies and properties to electrochemical supercapacitors is being intensively studied in order to provide enhanced energy density without comprising their inherent high power density and excellent cyclability. In particular, electrode materials that exploit physical adsorption or redox reactions of electrolyte ions are foreseen to bridge the performance disparity between batteries with high energy density and capacitors with high power density. In this review, we present some of the novel nanomaterial systems applied for electrochemical supercapacitors and show how material morphology, chemistry and physical properties are being tailored to provide enhanced electrochemical supercapacitor performance.